A highly stretchable and intrinsically self-healing strain sensor produced by 3D printing. (8th December 2020) - Guo, Binbin; Ji, Xinzhu; Chen, Xiaoteng; Li, Gang; Lu, Yongguang; Bai, Jiaming
ABSTRACT: One common issue when implementing wearable strain sensors for health-monitoring is the limited service time when they are inevitably subjected to mechanical operation in practical applications. Therefore, integrating multi-functionality with reliable performance is a long-term pursing target. To this end, we have developed a promising strain sensor utilising a facile 3D printing technology of digital light processing (DLP), thereby simultaneously realising super-high stretchability and intrinsic self-healing ability. Owing to the incorporation of carboxyl multi-walled carbon nanotubes (c-CNTs), the over-curing of the N-acryloylmorpholine (ACMO) resin was adequately mitigated, and good electrical conductivity of the nanocomposite was obtained. On the basis of multi-functionality, the strain sensor before and after self-healing can be applied for real-time and accurate detection of human activities. Therefore, it is expected that the highly stretchable and intrinsically self-healing strain sensor will have promising applications in wearable electronics, personal health care, etc. GRAPHICAL ABSTRACT: